Knowledge discovery, knowledge engineering and knowledge management : 10th International Joint Conference, IC3K 2018, Seville, Spain, September 18-20, 2018, Revised selected papers /: 10th International Joint Conference, IC3K 2018, Seville, Spain, September 18-20, 2018, Revised selected papers. (2020) - Unknown
No abstract available